1998
DOI: 10.1143/jjap.37.1427
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reliable Operation of InGaAlAs Waveguide Photodiodes for Optical Access Network Systems

Abstract: Reliability of InGaAlAs mesa waveguide photodiodes suitable for low-cost modules applied to access network systems is investigated. Stable operation for 9600 hours has been confirmed so far in the bias-temperature accelerated aging test. Median lifetime at a field service temperature of 85°C is estimated to be over 100 years by using the measured activation energy of 0.48 eV. Change in dark current during aging is explained by the hole accumulation at the interface between a crystal surface and a passiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…After the reliability testing of the WGPD test structures, the failure analysis on the thermally and electrically stressed WGPD test structures was carried out using the scanning electron microscopy (SEM) and the energy dispersive spectrometry (EDS). The degradation mechanisms for mesa-structure photodiodes have been reported by several researchers [3]- [5]. It was reported that one of the main reasons for the increase in dark current, which causes the failure of the devices, is the leakage path at the exposed surface of the p-n junction between the semiconductor and the passivated dielectric film.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the reliability testing of the WGPD test structures, the failure analysis on the thermally and electrically stressed WGPD test structures was carried out using the scanning electron microscopy (SEM) and the energy dispersive spectrometry (EDS). The degradation mechanisms for mesa-structure photodiodes have been reported by several researchers [3]- [5]. It was reported that one of the main reasons for the increase in dark current, which causes the failure of the devices, is the leakage path at the exposed surface of the p-n junction between the semiconductor and the passivated dielectric film.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that one of the main reasons for the increase in dark current, which causes the failure of the devices, is the leakage path at the exposed surface of the p-n junction between the semiconductor and the passivated dielectric film. It was proposed that the leakage path is formed by hole accumulation near lateral junction or accumulation of mobile ions in passivation film due to electric field [3]. Prior to the analysis, the presence of contaminants in passivating nitride and polyimide at the exposed junction was assumed as a possible cause for the dark current increase during the testing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations